Estimating milk production and energy-use efficiency of pasture-grazed Holstein and Jersey cows using mathematical models - Bangani, N.M.; Muller, C.J.C.; Dzama, K.; Cruywagen, C.W.C; Nherera-Chokuda, F.V.; Imbayarwo-Chikosi, V.E. (South African journal of animal science, 2023)
The efficiency of feed use for milk production is critical for sustainable and profitable pasture-based dairy systems. The aim of this study was to estimate milk production and energy-use efficiencies of pasture-grazed Holstein and Jersey cows. Lactation records of 122 Holstein and 99 Jersey cows varying from parities 1 to 6 that were managed under similar feeding and environmental conditions were collected from 2005 to 2014. Feed intake and nutrient requirements of the cows were calculated using the National Research Council and the Cornell Net Carbohydrate and Protein System equations. Holsteins had a higher milk yield/kg dry matter intake (1.36±0.01 vs. 1.27±0.01 kg), whereas Jerseys had higher efficiencies in milk fat (52.4±0.3 vs. 58.4±0.4 g), milk protein (42.7±0.3 vs. 45.1±0.3 g), and energy-corrected milk (1.30±0.01 vs. 1.36±0.01 kg) per kg dry matter intake. Jersey cows also had a higher dry matter intake/kg body weight (3.13±0.02 vs. 3.51±0.02%). During transition and early lactation stages, Holstein and Jersey cows were in negative energy balance for 102.4±2.3 vs. 74.2±2.3 days, with the lowest energy reserves (-53.9 MJ vs. -39.7 MJ) reached at 22.3±0.9 vs. 24.6±0.9 days post-calving, respectively. Compared to Holsteins, Jersey cows used proportionally less net energy intake to produce 100 g milk fat (13.7±0.10 vs. 12.5±0.10), 100 g milk protein (16.7±0.14 vs.16.2±0.15) and a 1-kg energy-corrected milk (5.52±0.04 vs. 5.35±0.04), making them a better breed for pasture-based dairy systems as they possess more production and feed-use efficiency traits, which are desirable in pasture-based production systems.